Increasing The Competitive Advantage Of Sharia Rural Financing Banks (BPRS) Products Through A Marketing Mix Strategy: The Approach Of Hermawan Kartajaya And Muhammad Syakir Sula - Sudirjo, Frans; Zunaidi, Arif; Septiana, Aldila (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
This research aims to analyze the marketing strategy implemented by BPRS Lantabur Tebuireng Gresik Branch to increase the competitive advantage of Tadhabbur savings products by considering the approaches of Hermawan Kartajaya and Muhammad Syakir Sula. The research method used involved interviews with BPRS marketing managers, direct on-site observation, and literature studies to understand relevant marketing principles. Research found that BPRS Lantabur Tebuireng was successful in implementing a holistic marketing strategy. They offer products that suit customer needs, set competitive prices, carry out promotions through sharia financial education, provide responsive service, utilize technology, and implement social engagement programs. The success of this strategy is supported by high service quality, synergy with local communities, a focus on ethical values, and a humanist approach to marketing. These findings indicate that this approach can be used as an effective model for other Islamic financial institutions to increase the competitive advantage of their products. Thus, implementing a marketing strategy that is holistic and based on sharia values and community welfare can be the basis for strengthening the market position of sharia financial institutions in the banking industry.